Primer registro de anidamiento de la tortuga marina Chelonia agassizi en Punta Ratón, Honduras - Cruz, Gustavo A.; Espiral, Mario; Meléndez, Orlando (Revista de Biología Tropical, 1987)
The Presence of Chelonia agassizi is confirmed in the Golfo de Fonseca, Honduras. A single female was observed laying 67 eggs in Punta Ratón. The mean of meristic counts of four neonates after 47 days of natural incubation are: carapace length 44.9 mm., carapace width 35.7 mm., plastron length 35.9 mm., head width 14.3 mm., vertebral scales 5.7 , lateral scales 4-4 .2, marginal scales 11.7-12, nucal scale 2, postorbital scales 3.2-3.5.